Value of Peak Expiratory Flow Rate in Evaluating Cough Ability in Patients Undergoing Lung Surgery - Gui-Xian Liu; Jian-Hua Su; Xin Wang; Jin-Tao He (Canadian Respiratory Journal)
Introduction. Postoperative ineffective cough is easy to occur after thoracic surgery, and it is also a risk factor for postoperative pulmonary complications (PPCs). Objectives. To explore the value of peak expiratory flow rate (PEF) in evaluating cough ability in patients undergoing lung surgery and evaluate the effectiveness of chest wall compression during the expiratory phase by PEF. Methods. From September 2020 to May 2021, the researchers collected the data of patients who underwent lung surgery. Eventually, 153 patients who met the criteria were included, 102 cases were included in the effective cough group and 51 cases were included in the ineffective cough group. The receiver working curve (ROC curve) was used to analyze whether PEF could evaluate cough ability. At the same time, the researchers collected the pulmonary function data of the first 30 patients of the ineffective cough group while compressing the chest wall during the expiratory phase to evaluate the effectiveness of chest wall compression. Results. The area under the curve (AUC) of postoperative PEF to evaluate the postoperative cough ability was 0.955 (95% CI: 0.927–0.983, P<0.001). The values of PEF (127.17 ± 34.72 L/min vs. 100.70 ± 29.98 L/min, P<0.001, 95% CI: 18.34–34.59) and FEV1 (0.72 (0.68–0.97) L vs. 0.64 (0.56–0.82) L, P<0.001) measured while compressing the chest wall were higher than those without compression. Conclusions. PEF can be used as a quantitative indicator of cough ability. Chest wall compression could improve cough ability for patients who have ineffective cough.